Helical tubular photobioreactor design using computational fluid dynamics - García Barbosa, Arnol Smith; Antequera Cantillo, Daniel Andres; Arango Restrepo, Juan Pablo; Gómez Pérez, César Augusto; Espinosa Oviedo, Jairo José (CT&F - Ciencia, Tecnología y Futuro, 2020)
In this paper we present the design problem of helical tubular PhotoBioReactors (PBR) based on energy consumption minimization, using the radius of curvature for the cultivation of microalgae. Computational Fluid Dynamics (CFD) is used to design a configuration of the helical pipeline with minimum energy consumption. We determined how flow direction changes affect energy consumption. Additionally, it was found that the radius of curvature affects the pressure drop in the PBR’s pipe, so a cost function has been developed to solve an optimization problem seeking to obtain the optimum radius of curvature and a helical tubular PBR design with low pumping rates.